Colocasia esculanta Linn : Cultivation in Dabhara block in Janjgir – Champa district, Chhattisgarh in central India - Patel, D K (Journal of Phytology, 2013)
Colocasia esculanta Linn. is an annual herbaceous plant with small corms in side of the soil. All the plant parts are used as vegetable as well as medicinal purpose among the rural peoples. It is also a source of economic increment to the farmers. The study based on the assessing the cultivation of the Colocasia esculanta Linn. in Janjgir – Champa district of central part of Chhattisgarh state. The plant is also referred as a commercial crop. Many flavonoides and steroids have been isolated from Colocasia esculanta Linn. The plant is grown in India for especially its corm, leaves etc. India is marked as a center of origin of this plant. Plant produces more corms in sandy-black soil but capable to grow in all type of the soil, so it is cultivated over the state. During cultivation Well soil preparation, fertilizers, weed, disease etc. management is required. Out of them well water discharge from cultivated field play a key role for successful growth and development of the plant.The present paper focused on the cultivation and use of the Colocasia esculanta Linn in the Study area.